2011
DOI: 10.1016/j.hydromet.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of indium from indium tin oxide by solvent extraction

Abstract: All in-text references underlined in blue are linked to publications on ResearchGate, letting you access and read them immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
127
1
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(139 citation statements)
references
References 11 publications
2
127
1
9
Order By: Relevance
“…Toward the development of recovery techniques of In(III) and Ga(III), a variety of extractants such as organic phosphoric acids [2][3][4][5][6][7][8][9], amines [10,11], carboxylic acids [12] and oximes [6,12,13] have been actively studied for the selective extraction of In (III) and Ga (III). Gupta et al reported that In (III) and Ga (III) were qualitative extracted at hydrochloric acid concentrations of over 0.01 M(= mol dm -3 ) and 1 M hydrochloric acids, respectively when Cyanex 923 in toluene was used [14].…”
Section: Introductionmentioning
confidence: 99%
“…Toward the development of recovery techniques of In(III) and Ga(III), a variety of extractants such as organic phosphoric acids [2][3][4][5][6][7][8][9], amines [10,11], carboxylic acids [12] and oximes [6,12,13] have been actively studied for the selective extraction of In (III) and Ga (III). Gupta et al reported that In (III) and Ga (III) were qualitative extracted at hydrochloric acid concentrations of over 0.01 M(= mol dm -3 ) and 1 M hydrochloric acids, respectively when Cyanex 923 in toluene was used [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, other than the refinery production, the reclaim processing of indium from secondary materials also become important [1,2,4]. The ITO-scrap is the most potential secondary resource of indium that extensively studied for the recovery of indium [3][4][5][6], while the etching waste [7,8] and the LCD powder [4,9,10] are the other prospective waste resources of indium.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the environmental impact, an assuming possibility of indium-induced cytotoxicity and the risk for interstitial lung damage due to the emission of sparingly soluble indium compounds from the ITO manufacturing and recycling plant have been reported [8,13,14]. Although the reclamation of indium from LCD-waste using a safer and cleaner process is becoming an increasing concern in terms of the economics, environment or owing to the possibility of toxic exposure, a few research reports are available in the literature [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…China, South Korea). Hence, the recovery of indium from the waste resources received sincere focus from the researches [4-6].The ITO-scrap resulted from the ITO ceramic target during the conversion and application of ITO thin films on glass panels using the DC magnetron sputtering process is the most potential secondary resource of indium [2,3,6,7]. The other prospective waste resources of indium are the etching waste [1,8] and the LCD powder [6,9].…”
mentioning
confidence: 99%